Permanent His‐Bundle Pacing: Case Studies. Issue 12 (23rd July 2016) - VIJAYARAMAN, PUGAZHENDHI; DANDAMUDI, GOPI
Abstract : His bundle pacing (HBP) is a physiological alternative to right ventricular pacing. In addition to patients with normal His‐Purkinje conduction, HBP can be valuable in patients with infranodal atrioventricular (AV) block and patients undergoing AV node ablation. The following case studies illustrate the challenges associated with HBP.